Flooding and child development: Evidence from Vietnam - My Tra Nguyen; Kien Le (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
This study examines the extent to which recent exposure to flooding influences the development outcomes (education and health) of Vietnamese children. Given children’s higher vulnerability to the threat of extreme weather events compared to the general population, it is important to study the impacts of flooding on child development. To do so, we draw from a panel dataset of children (the Young Lives Project) from five provinces of Vietnam (Phu Yen, Ben Tre, Lao Cai, Hung Yen, and Da Nang) where children were followed over 15 years. The flooding measure from the data is a self-reported measure as household indicates whether they have been recently affected by flooding. Regarding the empirical method, we employ the child-fixed effects model. We find that recent exposure to flood shocks makes children 3.3 percentage points less likely to enroll in school and score 0.21 and 0.24 standard deviations lower in math and reading achievement tests, respectively. They are also 0.11 standard deviations thinner in height, 3.8 percentage points more likely to be underweight, and 0.27 points lower in subjective well-being. Our mechanism analyses show that the adverse impacts of flooding on child development could be ascribed to the declines in food expenditure and household wealth as well as the increase in the amount of time spent on productive activities such as housework. Specifically, flooding could decrease food expenditure and household wealth, which, as a result, leads to insufficient food intake, thus worsening child health and nutrition status. Flooding might also induce households to substitute adult labor in unpaid housework with child labor, leading children to divert their time away from studying to doing household chores, and thus their schooling outcomes suffer.